Patterns of smoking and its association with psychosocial work conditions among blue-collar and service employees of hospitality venues in Shenyang, PR China - Guan Peng; Li Xuelian; Liang Huiying; Li Xun; Yin Zhihua; Zhou Baosen (BMC, 2010)
Abstract Background To characterize the smoking patterns of hospitality employees in blue-collar and service occupations, and to examine its relations with psychosocial work conditions. Methods The Shenyang Hospitality Industry Employees Survey-a face-to-face cross-sectional study of representative hospitality industry employees-was conducted between March and July 2008. A total of 4,213 workers were selected using stratified random cluster sampling designs, and final analyses were performed on 2,508 blue-collar and service subjects. Multilevel-logistic regression models were used to estimate the contribution of psychosocial work conditions to smoking status. Results Blue-collar and service employees smoked at a rate 1.4 times that of the general population (49.4% vs. 35.8%), more particularly for females (12.9% vs. 3.08%). Strain jobs had significantly higher odds ratio of daily smoking (OR 2.09, 95%CI: 1.28-3.41) compared to the relaxed category. The passive jobs (OR 2.01, 95%CI 1.27 to 3.17), highest job demands (OR 1.72, 95%CI: 1.13-2.61), and lowest job control (OR 2.56, 95%CI: 1.57-4.16) were also associated with a significantly higher daily smoking ratio. The negative relationship between job stability and smoking behavior was slightly stronger among daily than occasional smokers. However, neither job strain nor any of its components was found to be significantly associated with occasional smoking. Conclusions Smoking in hospitality blue-collar and service employees is certainly a major occupational health problem in Shenyang. This evidence also suggests an association between psychosocial-work conditions and smoking status, and implies that more intervention studies where changes in work environment are carried out in combination with health promotion interventions should be performed.